2022
DOI: 10.3390/cells11111746
|View full text |Cite
|
Sign up to set email alerts
|

Circ0001470 Acts as a miR-140-3p Sponge to Facilitate the Progression of Embryonic Development through Regulating PTGFR Expression

Abstract: Embryonic implantation and development are vital in early pregnancy and assisted reproduction. Circular RNAs (circRNAs) are involved in the two physiological processes and thus regulate animal reproduction. However, their specific regulatory functions and mechanisms remain unclear. Here, a novel circ0001470, originating from the porcine GRN gene, differentially expressed on day 18 versus day 32 of gestation in Meishan and Yorkshire pigs was screened. The circularization characteristic of circ0001470 was identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In recent years, with the development of high-tech sequencing technology, a large number of circRNAs have been discovered in mammals. More and more studies have shown that circRNAs play a pivotal role in regulating cell proliferation, apoptosis, and differentiation [ 37 , 38 ]. circRNAs are formed by reverse splicing without 5′ cap and 3′ poly tails; Thus, circRNAs are more stable due to their resistance to RNase [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the development of high-tech sequencing technology, a large number of circRNAs have been discovered in mammals. More and more studies have shown that circRNAs play a pivotal role in regulating cell proliferation, apoptosis, and differentiation [ 37 , 38 ]. circRNAs are formed by reverse splicing without 5′ cap and 3′ poly tails; Thus, circRNAs are more stable due to their resistance to RNase [ 19 ].…”
Section: Discussionmentioning
confidence: 99%